The Bulgarian State and the „inner other“ - Bakalova, Mariq (Research Papers, 2019)
The study examines the problem of the relevant “internal other” in the modern Bulgarian state. The author’s thesis is that from the creation of the third Bulgarian state to present days the attitude and the politics towards the “internal other” reveals two opposing trends – the “inclusive Republicanism” stemming from Vassil Levski’s ideas, and the defensive non recognition and/or exclusion of “internal others”. The dynamics of these trends depends on the active impact and the role of external factors of ideological and political nature. The retrospective review and analysis reveals that the development of attitudes towards "the internal one" is uneven, even crisscrossing because of the complexity of interdependent external influences and inner perceptions and positions. The two tendencies should not be considered mutually exclusive, because vital and effective appear to be policies that combine aspects of both tendencies.